Designing a Content Marketing Strategy Through the Utilization of Social Media Platforms in an Effort to Increase Brand Awareness Among Customers: A Case Study of ELCOFFEE.ID - Lubis, Abdillah Rizky Ananta; Hasibuan, Ali Fikri (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze and evaluate the effectiveness of content marketing strategies implemented through Instagram @elcoffee.id.official in increasing brand awareness among El Coffee customers. This study uses mixed methods with a cross-sectional design, integrating quantitative and qualitative data. The results show that the content marketing strategy design implemented on the Instagram account @elcoffee.id.official significantly increases brand awareness among El Coffee customers. The increase in account performance is seen from the number of views that jumped from 16,800 to 38,500, interactions from 11 to 991, and the addition of new followers from 83 to 132 accounts in one month. Informative, visually aesthetic, promotional, and interactive content proved effective in driving engagement. The results of descriptive statistical tests showed an average value of content marketing of 63.53 (high) and brand awareness of 35.97 (high). The t-test proved a significant effect of the content marketing variable on brand awareness with a t-value of 11.721 and a significance of 0.001 (less than 0.05). This increase shows that a planned and consistent content marketing strategy is able to strengthen brand recognition and recall among customers.